Transactional Leadership, Work Discipline, and Job Satisfaction in Elementary School Teacher Performance: A Study in Pondok Aren District, South Tangerang - Eti Rosmiati; Ruknan Ruknan; Yulita Pujilestari (Actual Insight, 2025)
Teacher performance is a crucial determinant of educational quality, as it directly influences the effectiveness of teaching and learning processes. This study examines the effects of transactional leadership, work discipline, and job satisfaction on the performance of elementary school teachers in Pondok Aren District, South Tangerang City. Employing a quantitative research design, the study involved a representative sample of teachers selected through proportional sampling techniques. Data were collected using structured questionnaires and analyzed using statistical methods to determine both partial and simultaneous effects of the independent variables on teacher performance. The findings indicate that transactional leadership has a significant positive influence on teacher performance by clarifying expectations, reinforcing accountability, and providing contingent rewards. Work discipline also demonstrates a strong positive effect, reflecting the importance of compliance with rules, time management, and professional responsibility in sustaining optimal performance. In addition, job satisfaction contributes positively by enhancing teachers’ motivation, commitment, and engagement in their professional roles. Simultaneously, transactional leadership, work discipline, and job satisfaction collectively exert a significant influence on teacher performance. These results suggest that improving teacher performance requires an integrated approach that combines effective leadership practices, disciplined work behavior, and supportive organizational conditions that foster job satisfaction. The study provides practical implications for school leaders and policymakers in designing strategies to enhance teacher performance and overall educational quality.